HUBUNGAN ROTASI JABATAN DAN MOTIVASI KERJA PADA ANGGOTA KEPOLISIAN FUNGSI TURJAWALI POLRES SLEMAN - Addintya Rahman Hakim; Berliana Henu Cahyani (Universitas Sarjanawiyata Tamansiswa, 2014)
ABSTRACTThis research aimed to determine the relation of job rotation with work motivation in POLRES Sleman. This research is conducted in quantitative approach, using two and Subjects in this study were staff of Turjawali POLRES Sleman. Data was collected with tour of duty scale and job motivation scale.Â Data was analyzed using SPSS (Statistical Packages for Social Science) for windows release version 17.0.The result showed a positive significant relationship between tour of duty with job motivation in the case of staff Turjawali POLRES Sleman. The coefficient of determination () is 0,889 or 88,9%, this means job rotation can predict job motivation variable (Y) of 88,9% and the rest remaining 11,1% can be explained or predicted by other factors. So, the higher job rotation it would be impact to the higher work motivation to the worker, otherwise the lower of job rotation then the lower of work motivation staff.Keyword: Job rotation, work motivation